Perbandingan Ekstrak Warna Daun Jati (Tectona Grandis) Dan Ekstrak Warna Daun Pacar (Lawsonia Inermis L) Terhadap Hasil Pewarnaan Rambut - Zulfina Rahmah Dinda; Mimi Yupelmi (Student Scientific Creativity Journal, 2024)
People really like hair coloring. However, most people do not know about natural dyes that can be used as basic ingredients for making hair dye and also lack understanding in choosing natural dyes used for coloring. For this reason, safe alternative dyes are needed, namely by developing natural dyes from plants that can be found nearby. This research aims to a) Analyze the results of hair coloring using teak leaf color extract, b) Analyze the results of hair coloring using henna leaf color extract, c) Analyze the comparison of hair coloring results using duan teak color extract and henna leaf color extract. This type of research is pre-experimental. The design used is a one shot case study. The population of this research is students of Cosmetology and Beauty, Class of 2023, Padang State University with 6 samples and 7 panelists. Data collection techniques are observation, documentation and questionnaire methods. The data analysis techniques used are normality test, homogeneity test and t test. Based on the results of research on hair coloring using teak leaf color extract, the color sharpness aspect is in the sharp category. In terms of evenness, the color has an uneven category. In terms of likes, panelists have categories of likes. Based on the results of research on hair coloring using henna leaf color extract, the color sharpness aspect is in the very sharp category. In the aspect of color evenness, it has an average category. In terms of likes, the panelists have a very like category. It can be concluded that there is a difference in the results of hair coloring using teak leaf color extract and henna leaf color extract. Where the average results of hair coloring using henna leaves are better than hair coloring using henna leaf color extract.